2017
DOI: 10.1002/bies.201700159
|View full text |Cite
|
Sign up to set email alerts
|

Noise in the Machine: Alternative Pathway Sampling is the Rule During DNA Replication

Abstract: The astonishing efficiency and accuracy of DNA replication has long suggested that refined rules enforce a single highly reproducible sequence of molecular events during the process. This view was solidified by early demonstrations that DNA unwinding and synthesis are coupled within a stable molecular factory, known as the replisome, which consists of conserved components that each play unique and complementary roles. However, recent single-molecule observations of replisome dynamics have begun to challenge th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 128 publications
(296 reference statements)
0
15
0
Order By: Relevance
“…Our observations and previous studies (Douglas et al, 2018; Langston et al, 2014; Lewis et al, 2017b) suggest that Pol ε is a stable component of the replisome. However, recent single-molecule experiments have demonstrated that stable components of multi-protein complexes can undergo dynamic exchange when challenged with competing binding partners (Delalez et al, 2010; Graham et al, 2011; Li et al, 2019; Scherr et al, 2018). In particular, complexes held together by multiple weak interactions support high stability in the absence of competing factors but rapid exchange in the presence thereof (van Oijen and Dixon, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Our observations and previous studies (Douglas et al, 2018; Langston et al, 2014; Lewis et al, 2017b) suggest that Pol ε is a stable component of the replisome. However, recent single-molecule experiments have demonstrated that stable components of multi-protein complexes can undergo dynamic exchange when challenged with competing binding partners (Delalez et al, 2010; Graham et al, 2011; Li et al, 2019; Scherr et al, 2018). In particular, complexes held together by multiple weak interactions support high stability in the absence of competing factors but rapid exchange in the presence thereof (van Oijen and Dixon, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Instead a physical encounter is likely required to convert transient breaks into irreversible breaks 30 that are ultimately exposed to the cell during failed repair attempts 31 . The improved throughput of FMT allows for direct characterization of the dynamics of encounters of complex machineries 32 , which were previously out of reach.…”
Section: Discussionmentioning
confidence: 99%
“…Recent single-molecule studies have revealed the dynamic behavior of proteins involved in DNA replication. This has changed our view of the replisome from a neat and deterministic machine, to a more "messy" and stochastic system of proteins (Åberg et al 2016;Geertsema and van Oijen 2013;Scherr et al 2018;Xu and Dixon 2018). Proteins bind to the replisome through a plurality of weak interactions.…”
Section: Discussionmentioning
confidence: 99%